Finite element analysis and fracture resistance testing of a new intraradicular post - Yamamoto, Eron Toshio Colauto [UNESP]; Pagani, Clovis [UNESP]; da Silva, Eduardo Galera [UNESP]; Noritomi, Pedro Yoshito; Uehara, André Yugou; Kemmoku, Daniel Takanori (FapUNIFESP (SciELO), 2012)
ObjectiveS: The objective of the present study was to evaluate a prefabricated intraradicular threaded pure titanium post, designed and developed at the São José dos Campos School of Dentistry - UNESP, Brazil. This new post was designed to minimize stresses observed with prefabricated post systems and to improve cost-benefits. Material and Methods: Fracture resistance testing of the post/core/root complex, fracture analysis by microscopy and stress analysis by the finite element method were used for post evaluation. The following four prefabricated metal post systems were analyzed: group 1, experimental post; group 2, modification of the experimental post; group 3, Flexi Post, and group 4, Para Post. For the analysis of fracture resistance, 40 bovine teeth were randomly assigned to the four groups (n=10) and used for the fabrication of test specimens simulating the situation in the mouth. The test specimens were subjected to compressive strength testing until fracture in an EMIC universal testing machine. After fracture of the test specimens, their roots were sectioned and analyzed by microscopy. For the finite element method, specimens of the fracture resistance test were simulated by computer modeling to determine the stress distribution pattern in the post systems studied. Results: The fracture test presented the following averages and standard deviation: G1 (45.63±8.77), G2 (49.98±7.08), G3 (43.84±5.52), G4 (47.61±7.23). Stress was homogenously distributed along the body of the intraradicular post in group 1, whereas high stress concentrations in certain regions were observed in the other groups. These stress concentrations in the body of the post induced the same stress concentration in root dentin. ConclusionS: The experimental post (original and modified versions) presented similar fracture resistance and better results in the stress analysis when compared with the commercial post systems tested (08/2008-PA/CEP).
Keywords: Finite element analysis; Post and core technique; Stress fractures